THE EFFECT OF TAPIOCA FLOUR AND MOCAF ADDITION ON THE CHEMICAL CHARACTERISTIC OF SEAWEED CRACKERS - Ramadhini, Tri Karimah; Ardhanawinata, Adlina; Diachanty , Seftylia; Irawan, Irman (Universitas Mataram, 2025)
This study evaluated the effect of substituting tapioca flour and Modified Cassava Flour (MOCAF) on the chemical characteristics of crackers formulated with Kappaphycus alvarezii seaweed. Four treatments were prepared with varying proportions of seaweed, tapioca flour, and MOCAF. Chemical analyses included measurements of moisture, ash, protein, fat, carbohydrate and crude fiber content. Results showed that increasing the proportion of seaweed consistently elevated moisture content (5.32-9.23%), ash content (0.98-2.02%), protein content (2.47-4.04%), fat content (0.29-0.52%), carbohydrate content (84.19-90.95%) and crude fiber (1.57-4.04%) levels in the raw crackers. The highest values across all parameters were observed in treatment KR4 (32% seaweed), whereas the lowest values were recorded in treatment KR1 (without seaweed addition). Moisture, ash, and fat content in all treatments complied with the Indonesian National Standard (SNI) for raw crackers. The enhancement in chemical characteristics were primarily attributed to the naturally high levels of fiber, hydrocolloids, minerals, and protein present in Kappaphycus alvarezii seaweed. These findings demonstrate that partial substitution of tapioca and MOCAF flours with seaweed enhances the nutritional profile of crackers, thus potentially yielding products with greater functional value.